Overall seismic risk in Bosnia-Herzegovina/Dalmatia region of Croatia and elements of perfect crisis in an earthquake aftermath - Smailbegović, Amer (Array, 2020)
Bosnia-Herzegovina and southern-coastal/hinterland-region of Dalmatia, Republic of Croatia are a part of the same seismo-tectonic province and share a considerable and real threat of high-magnitude earthquakes. Numerous Magnitude 6 (Richter) and above earthquakes have been recorded in the past 500 years and some of them have resulted in a considerable loss of life, material and even prestige or geopolitical significance (e.g. the demise of Ragusa in the earthquake of 1667). Given the propensity of the region for destructive earthquakes, complex geomorphological framework and challenging infrastructure, still recovering in parts from the Yugoslav civil wars of the 1990s., the region may yield a “perfect” crisis in the aftermath of a major earthquake event. Taking into consideration unchecked development of several metropolitan areas, lack of oversight and permitting, decaying infrastructure as well as unresolved political ambiguities and territorial disputes, a potential destructive earthquake may create several cascading crises, especially if it coincides with some other challenging events (e.g. winter storms). This study is taking into consideration several scenarios, their possible effects and resulting conditions upon which cascading crises may arise in the aftermath of a magnitude 7+ earthquake affecting several major urban areas in southern and central Bosnia-Herzegovina and the southern Dalmatian region of Croatia. These scenarios are intended to provide training aids and risk assessments in countering the destructive forces after the earthquake, expected to test the current crisis-management models.